Phylogenetic classification and generic delineation of Hydeomyces desertipleosporoides gen. et sp. nov., (Phaeosphaeriaceae) from Jebel Akhdar Mountain in Oman - Maharachchikumbura, Sajeewa S. N.; Ariyawansa, Hiran A.; Wanasinghe, Dhanushka N.; Dayarathne, Monika C.; Al-Saady, Nadiya A.; Al-Sadi, Abdullah M. (Phytotaxa, 2019)
Specimens of a new pleosporalean taxon were obtained on the bark of Juniperus excels from the northern mountains of Oman; from the Jebel Akhdar (‘Green Hills’). Sequence analyses based on the regions of large subunit rRNA (LSU), small subunit rRNA (SSU), translation elongation factor 1-α (TEF) and internal transcribed spacers (ITS) were performed to resolve the phylogenetic relationships of the new taxon in Phaeosphaeriaceae. The data concluded that the taxon represents a novel genus of the family Phaeosphaeriaceae and the generic name Hydeomyces and the species name H. desertipleosporoides are introduced for the new taxon. An outline of the characters which differentiate the new genus from phylogenetically closely related genera Dematiopleospora and Dlhawksworthia is given and its morphology of asexual and sexual morphs is described.